Wandering Spleen with Torsion Causing Pancreatic Volvulus and Associated Intrathoracic Gastric Volvulus: An Unusual Triad and Cause of Acute Abdominal Pain - Aswani, Yashant; Anandpara, Karan Manoj; Hira, Priya (JOP. Journal of the Pancreas, 2015)
Context Wandering spleen is a rare medical entity in which the spleen is orphaned of its usual peritoneal attachments and thus assumes an ever wandering and hypermobile state. This laxity of attachments may even cause torsion of the splenic pedicle. Both gastric volvulus and wandering spleen share a common embryology owing to maldevelopment of the dorsal mesentery. Gastric volvulus complicating a wandering spleen is, however, an extremely unusual association, with a few cases described in literature. Case report We present a case of a young female who presented with acute abdominal pain and vomiting. Radiological imaging revealed a intrathoracic gastric volvulus, torsion in an ectopic spleen, and additionally demonstrated a pancreatic volvulus - an unusual triad, reported only once, causing an acute abdomen. Conclusion The patient subsequently underwent an emergency surgical laparotomy with splenopexy and gastropexy. Image: Grossly distended stomach with Ryle’s tube in situ.